Entrepreneurial Orientation and Marketing Innovation ON PERFORMANCE MARKETING WITH LEVEL OF COMPETITION AS INTERVENING VARIABLES (Survey on UMKM Actors in KUNIGAN DISTRICT) - Gunawan, Wely Hadi; Novandari, Weni; Setyanto, Refius Pradipta (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The phenomenon in this research is the market share, especially MSMEs in Kuningan Regency, which experienced a decline in sales from year to year. So it can be interpreted thatThe Kuningan Regency MSME market share experienced negative growth. This lessonaims to find out or analyze the influence of green marketing and corporate socialresponsibility for purchasing decisions through consumer knowledge. The sample taken was 150 MSMEs in Kuningan Regency. The research instrument was in the form of distributing questionnaires via Google from. The data analysis technique used is Structural Equation Modeling (SEM). The results of hypothesis testing show that (1) Entrepreneurial Orientation has a positive and significant influence on the Level of Competition. (2) Marketing Innovation has a significant positive impact on the Level of Competition. (3) Entrepreneurial Orientation has a positive and significant impact on Marketing Performance. (4) Marketing Innovation has no effect on Marketing Performance decisions. (5) The level of Interference has a positive effect on purchasing decisionsand has a positive effect on Important Marketing Performance. (6) Entrepreneurial Orientation has a positive effect on Marketing Performance through Marketing Innovation. (7) Marketing Innovation has a positive effect on Marketing Performance through Level